Anti-static PE plastic product

By adding carbon black conductive filler and antistatic agent to high-density polyethylene plastic, combined with color fixing agent and flame retardant, the problem of easy static disengagement of antistatic plastic products during transportation is solved, and its antistatic properties are improved. Wear resistance, maintains resistivity and conductivity.

CN119264546APending Publication Date: 2025-01-07XIONGXIAN LUCHENG PAPER PLASTIC PACKAGING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411589907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing anti-static plastic products are prone to electrostatic charges during transportation, installation and handling, and the anti-static agent coating method is easy to detach, resulting in unstable anti-static performance.

Method used

High-density polyethylene is used as the matrix, carbon black is added as the conductive filler, and a conductive filler and antistatic agent are formed through a specific preparation process. Combining the solidifying agent and flame retardant, it is melt blended and injection molded to ensure the adhesion of the antistatic agent. Stablize.

Benefits of technology

It improves the washing resistance, wear resistance and antistatic durability of plastic products, maintains volume resistivity, avoids flame retardants affecting antistatic properties while enhancing conductive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264546A_ABST
    Figure CN119264546A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-static PE plastic product, and relates to the technical field of anti-static plastic preparation. The antistatic PE plastic product comprises the following components in parts by weight: 100-150 parts of high-density polyethylene, 1-1.5 parts of an antioxidant, 30-50 parts of a conductive filler, 10-20 parts of an antistatic agent, 5-9 parts of a color fixing agent, 1-3 parts of trichloromethane, 2-3 parts of a flame retardant, 10-12 parts of a coupling agent and 3-8 parts of Sb2O3, and carbon black is selected as a base material of the conductive filler. By adding the color fixing agent, the antistatic agent can be stably attached to the interior and the surface of the plastic product, so that large-scale separation is not generated in drying, standing, washing and other operations in the preparation process, the washability and the wear resistance of the plastic product are finally improved, the antistatic durability of the plastic product is enhanced, and the volume resistivity of the plastic product is kept; and the antistatic agent is added in a blending manner, so that the prepared antistatic film has a long-term antistatic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of antistatic plastic preparation technology, specifically to an antistatic PE plastic product. Background Technology

[0002] Antistatic plastic products play a vital role in modern industry and technology. With the increasing prevalence and sophistication of electronic devices, the application of antistatic plastics not only ensures the normal operation of equipment but also greatly improves production efficiency and safety.

[0003] The core function of antistatic plastic products lies in their ability to effectively control and prevent the generation and accumulation of static electricity. Static electricity is a common physical phenomenon that generates static charge when two objects rub or separate. For many industries, static electricity can have serious consequences. For example, in the electronics industry, electrostatic discharge can damage sensitive electronic components, causing significant economic losses. Antistatic plastics, by adding special conductive materials or antistatic agents, form a conductive layer on the plastic surface, thereby rapidly releasing and dispersing static charge and avoiding the hazards caused by static accumulation. The aerospace industry is also an important application area for antistatic plastics. Aircraft fuselages and wings often use carbon fiber composite materials, which are highly susceptible to static electricity generation upon friction. Antistatic plastics are used for surface treatment of these components to reduce static electricity accumulation and prevent threats to flight safety.

[0004] For example, the antistatic packaging plastic film disclosed in Chinese Patent Publication No. CN114891291B uses high-density polyethylene as a matrix and incorporates an antistatic agent through blending. This avoids external coating, resulting in a long-lasting antistatic effect. The invention introduces a hyperbranched compound 'a' with a three-dimensional network structure. This compound exhibits high intermolecular regularity and is less prone to entanglement, leading to better dispersion of the synthesized antistatic agent within the matrix and enhanced antistatic performance. Furthermore, the unique three-dimensional macromolecular structure makes the antistatic agent more stable, expanding its application range. Additionally, the invention incorporates a modifying filler. First, the surface of nano-silica is treated with a silane coupling agent. Then, potassium sulfate is used as an initiator to polymerize the mixed monomers on the nano-silica, forming organic-inorganic composite core-shell structure particles, improving its compatibility with organic matter.

[0005] The above methods mainly address antistatic measures by changing the filler and abandoning existing coating methods, instead incorporating antistatic agents. However, in practical applications, it has been found that while antistatic agent coating can reduce the coefficient of friction on the surface of plastic products to some extent, the above methods, without coating, allow the resulting products to easily retain static charge during actual transportation, installation, and handling due to friction. Furthermore, the antistatic agent coating is prone to detachment. Therefore, a new preparation method is urgently needed that allows for continuous coating while incorporating antistatic agents, and where the coating is less likely to detach. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides an antistatic PE plastic product that solves the problems mentioned in the background section.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solution: an antistatic PE plastic product, comprising the following components in parts by weight: 100-150 parts high-density polyethylene, 1-1.5 parts antioxidant, 30-50 parts conductive filler, 10-20 parts antistatic agent, 5-9 parts color-fixing agent, 1-3 parts chloroform, 2-3 parts flame retardant, 10-12 parts coupling agent, and 3-8 parts Sb2O3, wherein the conductive filler substrate is selected as carbon black.

[0008] A further improvement to the technical solution of the present invention is that the preparation process of the conductive filler includes the following specific steps:

[0009] S1: Pass the carbon black through a 400-mesh sieve, weigh the carbon black and an appropriate amount of water into a beaker, heat and stir at the same time, and control the heating temperature at 61.5℃. After stirring and heating, the carbon black powder is evenly suspended on the water surface.

[0010] S2: Weigh out appropriate amounts of SnCl4·5H2O and SbCl3 and dissolve them in another beaker. After preparing to a suitable concentration, add them to the carbon black suspension solution.

[0011] S3: Add HCl to adjust the pH value to 7.0-7.4, and add NaOH solution dropwise. Under the controlled pH value, heat and stir to allow the added SnCl4·5H2O and SbCl3 to undergo a hydrolysis reaction. Stop adding NaOH dropwise after the hydrolysis occurs. Continue stirring for 20 minutes after the hydrolysis reaction is complete. The hydrolysis product is coated on the suspended carbon black particles.

[0012] S4: Filter the final beaker solution from S3, wash the filtered product with distilled water, and test with AgNO3 solution until no white precipitate is found. Finally, dry the moisture at 98℃, cool it at room temperature, and grind it to obtain the desired conductive filler material made of carbon black.

[0013] A further improvement of the technical solution of the present invention is that, in the carbon black material of S1, ω(C)≥98.72% and ω(S)≤0.17%.

[0014] A further improvement to the technical solution of the present invention is that the preparation of the antistatic agent includes the following specific steps:

[0015] Q1: Glycerol and catalyst are added to a reactor equipped with a gas inlet and outlet device, followed by stirring, vacuuming, and heating. The temperature is raised to 106.4℃ and the vacuum degree is 1.4MPa to completely dissolve the catalyst in glycerol.

[0016] Q2: Turn off the vacuum, add glycerol tristearate to react, introduce N2, maintain the N2 pressure at 0.17 MPa, continue heating to 247.8℃, and react for 45 min;

[0017] Q3: Turn off the heating and start cooling. Slowly add glycerol tristearate, controlling the cooling rate and the addition rate of glycerol tristearate. After cooling to 154.9℃, keep it at that temperature for 45 minutes. The reaction is complete. Cool to obtain the antistatic agent.

[0018] A further improvement to the technical solution of the present invention is that the preparation of the Pe plastic product includes the following specific steps:

[0019] T1: Dissolve the prepared antistatic agent in chloroform and add an appropriate amount of fixing agent to obtain a mixed antistatic agent. Sb2O3 has certain conductivity, which can enhance the antistatic properties of the obtained sample product. The addition of flame retardant is necessary because the conductive filler is made of carbon black, which reduces the flame retardancy of plastic products.

[0020] T2: The flame retardant is mixed with Sb2O3 to obtain a mixed flame retardant; Sb2O3 has certain electrical conductivity, which can enhance the antistatic properties of the obtained sample product. The addition of the flame retardant is because T3: High-density polyethylene, antioxidant, conductive filler and coupling agent are weighed according to the ratio and mixed with the products obtained from T1 and T2. The mixture is melt-blended on an extruder, extruded and granulated, and the resulting granules are dried at 83°C for 12 hours. Finally, standard samples are injected through an injection molding machine, and the samples are placed in the remaining liquid of the mixed antistatic agent.

[0021] A further improvement of the technical solution of the present invention is that the PE plastic product sample in T3 is immersed in the remaining antistatic agent solution, taken out after 2 hours and ensuring that the surface is completely coated, placed in an oven at 48°C for 2 hours to dry, and then placed at room temperature for 1 hour after being taken out.

[0022] A further improvement of the technical solution of the present invention is that the raw materials in T3 are melt-blended on a screw extruder, and finally extruded and granulated. The resulting granules are then injected into an injection molding machine. The nozzle temperature of the injection molding machine is controlled at 200°C, the molding cycle is set to 50s, the injection pressure is set to 78MPa, and the screw speed of the extruder is set to 100r / min.

[0023] A further improvement of the technical solution of the present invention is that the antioxidant is selected as antioxidant 168, the coupling agent is selected as KH-550, and the carbon black in the conductive filler is selected as YM-100B.

[0024] A further improvement of the technical solution of the present invention is that the flame retardant is selected as (NH4)2HPO4.

[0025] Compared with the prior art, the beneficial effects of the present invention are: by adding a color-fixing agent, the antistatic agent can be firmly attached to the inside and surface of the plastic product, so that large-scale detachment does not occur during drying, placement, washing and other operations during the preparation process, ultimately improving the washability and wear resistance of the plastic product, enhancing the antistatic durability of the plastic product, maintaining the volume resistivity of the plastic product, and the co-mixing of the antistatic agent makes the prepared antistatic film have a long-lasting antistatic effect.

[0026] The introduction of flame retardants creates a gas layer during combustion that isolates the plastic product from oxygen, thus achieving a flame-retardant effect. Furthermore, the Sb2O3 mixed with the flame retardant has conductive properties, thereby increasing conductivity while achieving a flame-retardant effect and preventing the flame retardant from affecting the antistatic properties of the plastic product. Attached Figure Description

[0027] Figure 1 A schematic diagram of the process for manufacturing antistatic PE plastic products;

[0028] Figure 2 A schematic diagram of the process for preparing antistatic agents in antistatic PE plastic products;

[0029] Figure 3 A schematic diagram of the process for preparing conductive fillers in antistatic PE plastic products;

[0030] Figure 4 Table of surface resistivity test results for antistatic PE plastic product I and antistatic PE plastic product II;

[0031] Figure 5 Line graphs showing the change in volume resistivity of antistatic PE plastic products I and II as a function of events;

[0032] Figure 6 Table of surface resistivity test results for antistatic PE plastic product I and antistatic PE plastic product III;

[0033] Figure 7 Table showing the test results for tensile strength, surface resistivity, and flammability of antistatic PE plastic products I and III. Detailed Implementation

[0034] Various exemplary embodiments, features, and aspects of this application will now be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings denote elements that have the same or similar functions. Although various aspects of the embodiments are shown in the drawings, they are not necessarily drawn to scale unless specifically indicated otherwise.

[0035] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments.

[0036] Furthermore, to better illustrate this application, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this application can be implemented without certain specific details. In some instances, methods, means, and elements well-known to those skilled in the art have not been described in detail in order to highlight the main points of this application.

[0037] Reference Figure 1 - Figure 7 The present invention discloses an antistatic PE plastic product comprising the following components in parts by weight: 100-150 parts high-density polyethylene, 1-1.5 parts antioxidant, 30-50 parts conductive filler, 10-20 parts antistatic agent, 5-9 parts color fixing agent, 1-3 parts chloroform, 2-3 parts flame retardant, 10-12 parts coupling agent, and 3-8 parts Sb2O3, wherein the conductive filler substrate is selected as carbon black.

[0038] The preparation process of conductive fillers includes the following specific steps:

[0039] S1: Pass the carbon black through a 400-mesh sieve, weigh the carbon black and an appropriate amount of water into a beaker, heat and stir at the same time, and control the heating temperature at 61.5℃. After stirring and heating, the carbon black powder is evenly suspended on the water surface.

[0040] S2: Weigh out an appropriate amount of SnCl4·5H2O and SbCl3 and dissolve them in another beaker. After preparing to a suitable concentration, add them to the carbon black suspension solution.

[0041] S3: Add HCl to adjust the pH value to 7.0-7.4, and add NaOH solution dropwise. Under the controlled pH value, heat and stir to make the added SnCl4·5H2O and SbCl3 undergo hydrolysis reaction. Stop adding NaOH dropwise after hydrolysis occurs. After the hydrolysis reaction is completed, continue stirring for 20 minutes. The hydrolysis product is coated on the suspended carbon black particles.

[0042] S4: Filter the final beaker solution from S3, wash the filtered product with distilled water, and test with AgNO3 solution until no white precipitate is found. Finally, dry the moisture at 98℃, cool it at room temperature, and grind it to obtain the desired conductive filler material made of carbon black.

[0043] In the S1 carbon black material, ω(C)≥98.72% and ω(S)≤0.17%.

[0044] The preparation of antistatic agents includes the following specific steps:

[0045] Q1: Glycerol and catalyst are added to a reactor equipped with a gas inlet and outlet device, followed by stirring, vacuuming, and heating. The temperature is raised to 106.4℃ and the vacuum degree is 1.4MPa to completely dissolve the catalyst in glycerol.

[0046] Q2: Turn off the vacuum, add glycerol tristearate to react, introduce N2, maintain the N2 pressure at 0.17 MPa, continue heating to 247.8℃, and react for 45 min;

[0047] Q3: Turn off the heating and start cooling. Slowly add glycerol tristearate, controlling the cooling rate and the addition rate of glycerol tristearate. After cooling to 154.9℃, keep it at that temperature for 45 minutes. The reaction is complete. Cool to obtain the antistatic agent.

[0048] The preparation of PE plastic products includes the following specific steps:

[0049] T1: Dissolve the prepared antistatic agent in chloroform, add an appropriate amount of fixing agent, and obtain a mixed antistatic agent;

[0050] T2: The flame retardant is mixed with Sb2O3 to obtain a mixed flame retardant; Sb2O3 has certain electrical conductivity, which can enhance the antistatic properties of the obtained sample product. The addition of the flame retardant is necessary because the conductive filler is made of carbon black, which reduces the flame retardancy of the plastic product.

[0051] T3: Weigh high-density polyethylene, antioxidant, conductive filler and coupling agent according to the ratio, mix with the products obtained from T1 and T2, melt blend on an extruder, extrude and granulate, dry the resulting granules at 83°C for 12 hours, and finally inject standard samples through an injection molding machine. The samples are placed in the remaining liquid of the mixed antistatic agent.

[0052] In T3, PE plastic product samples are immersed in the remaining antistatic agent solution, removed after 2 hours, ensuring complete surface coating, and dried in an oven at 48°C for 2 hours. After removal, they are left to dry at room temperature for 1 hour.

[0053] In T3, the raw materials are melt-blended on a screw extruder, and finally extruded and granulated. The resulting granules are then injected into an injection molding machine. The nozzle temperature of the injection molding machine is controlled at 200℃, the molding cycle is set to 50s, the injection pressure is set to 78MPa, and the screw speed of the extruder is set to 100r / min.

[0054] The antioxidant selected was Antioxidant 168, the coupling agent was KH-550, and the carbon black in the conductive filler was YM-100B.

[0055] The flame retardant chosen is (NH4)2HPO4.

[0056] Example 1: The antistatic PE plastic product comprises the following specific raw material components: 120 parts high-density polyethylene, 1 part antioxidant, 30 parts conductive filler, 10 parts antistatic agent, 2 parts flame retardant, 10 parts coupling agent, and 3 parts Sb2O3. The conductive filler substrate is selected as carbon black, the antioxidant is selected as antioxidant 168, the coupling agent is selected as KH-550, the carbon black in the conductive filler is selected as YM-100B, and the flame retardant is selected as (NH4)2HPO4.

[0057] The conductive filler was prepared by passing carbon black through a 400-mesh sieve. Carbon black and an appropriate amount of water were weighed into a beaker, and heated while stirring at a controlled temperature of 61.5℃. After heating and stirring, the carbon black powder was uniformly suspended on the water surface. Appropriate amounts of SnCl₄·5H₂O and SbCl₃ were weighed and dissolved in another beaker to a suitable concentration, which was then added to the carbon black suspension. HCl was added to adjust the pH to 7.0-7.4, and NaOH solution was added dropwise. Under the controlled pH conditions, the mixture was heated and stirred to ensure the added SnCl₄·5H₂O and SbCl₃ were evenly suspended on the water surface. L3 undergoes a hydrolysis reaction. After hydrolysis occurs, the addition of NaOH is stopped. After the hydrolysis reaction is complete, stirring continues for 20 minutes. The hydrolysis product coats the suspended carbon black particles. The final beaker solution of S3 is filtered, and the filtered product is washed with distilled water. The absence of white precipitate is determined by AgNO3 solution testing. Finally, the moisture is dried at 98℃ and cooled at room temperature. The final conductive filler material of the desired carbon black material is obtained by grinding. Among them, the carbon black material of S1 has ω(C)≥98.72% and ω(S)≤0.17%.

[0058] The antistatic agent was prepared by adding glycerol and catalyst to a reactor equipped with a gas inlet / outlet device, followed by stirring, vacuuming, and heating. The temperature was raised to 106.4℃ and the vacuum degree was 1.4MPa to completely dissolve the catalyst in the glycerol. The vacuum was then turned off, and glycerol tristearate was added to react. N2 was introduced and the N2 pressure was maintained at 0.17MPa. Heating was continued to raise the temperature to 247.8℃ and reacted for 45 minutes. Heating was then turned off and cooling began. Glycerol tristearate was slowly added, and the cooling rate and the addition rate of glycerol tristearate were controlled. After cooling to 154.9℃, the temperature was maintained for 45 minutes. The reaction was then completed, and the antistatic agent was obtained by cooling.

[0059] Finally, the preparation of antistatic PE plastic products begins. The prepared antistatic agent is dissolved in chloroform, and an appropriate amount of fixing agent is added to obtain a mixed antistatic agent. The flame retardant is mixed with Sb2O3 to obtain a mixed flame retardant. High-density polyethylene, antioxidant, conductive filler and coupling agent are weighed according to the ratio and mixed with the obtained product. The mixture is melt-blended on an extruder, extruded and granulated. The obtained granules are dried at 83°C for 12 hours. Finally, standard samples are injected through an injection molding machine. The samples are placed in the remaining liquid of the mixed antistatic agent.

[0060] In T3, PE plastic product samples are immersed in the remaining antistatic agent solution, removed after 2 hours, ensuring complete surface coating, and dried in a 48℃ oven for 2 hours. After removal, they are left at room temperature for 1 hour. The raw materials in T3 are melt-blended on a screw extruder, and finally extruded and granulated. The resulting granules are then injected into an injection molding machine with the nozzle temperature controlled at 200℃, the molding cycle set at 50s, the injection pressure set at 78MPa, and the extruder screw speed set at 100r / min.

[0061] Finally, antistatic PE plastic product I was obtained.

[0062] Example 2: The antistatic PE plastic product comprises the following specific raw material components: 120 parts high-density polyethylene, 1 part antioxidant, 30 parts conductive filler, 10 parts antistatic agent, 5 parts color fixing agent, 1 part chloroform, 2 parts flame retardant, 10 parts coupling agent, and 3 parts Sb2O3. The conductive filler substrate is selected as carbon black, the antioxidant is selected as antioxidant 168, the coupling agent is selected as KH-550, the carbon black in the conductive filler is selected as YM-100B, and the flame retardant is selected as (NH4)2HPO4.

[0063] The conductive filler was prepared by passing carbon black through a 400-mesh sieve. Carbon black and an appropriate amount of water were weighed into a beaker, and heated while stirring at a controlled temperature of 61.5℃. After heating and stirring, the carbon black powder was uniformly suspended on the water surface. Appropriate amounts of SnCl₄·5H₂O and SbCl₃ were weighed and dissolved in another beaker to a suitable concentration, which was then added to the carbon black suspension. HCl was added to adjust the pH to 7.0-7.4, and NaOH solution was added dropwise. Under the controlled pH conditions, the mixture was heated and stirred to ensure the added SnCl₄·5H₂O and SbCl₃ were evenly suspended on the water surface. L3 undergoes a hydrolysis reaction. After hydrolysis occurs, the addition of NaOH is stopped. After the hydrolysis reaction is complete, stirring continues for 20 minutes. The hydrolysis product coats the suspended carbon black particles. The final beaker solution of S3 is filtered, and the filtered product is washed with distilled water. The absence of white precipitate is determined by AgNO3 solution testing. Finally, the moisture is dried at 98℃ and cooled at room temperature. The final conductive filler material of the desired carbon black material is obtained by grinding. Among them, the carbon black material of S1 has ω(C)≥98.72% and ω(S)≤0.17%.

[0064] The antistatic agent was prepared by adding glycerol and catalyst to a reactor equipped with a gas inlet / outlet device, followed by stirring, vacuuming, and heating. The temperature was raised to 106.4℃ and the vacuum degree was 1.4MPa to completely dissolve the catalyst in the glycerol. The vacuum was then turned off, and glycerol tristearate was added to react. N2 was introduced and the N2 pressure was maintained at 0.17MPa. Heating was continued to raise the temperature to 247.8℃ and reacted for 45 minutes. Heating was then turned off and cooling began. Glycerol tristearate was slowly added, and the cooling rate and the addition rate of glycerol tristearate were controlled. After cooling to 154.9℃, the temperature was maintained for 45 minutes. The reaction was then completed, and the antistatic agent was obtained by cooling.

[0065] Finally, the preparation of antistatic PE plastic products begins. High-density polyethylene, antioxidants, conductive fillers, antistatic agents, and coupling agents are weighed according to the specified ratio. Flame retardants are mixed with Sb2O3 to obtain a mixed flame retardant. The mixed flame retardant is then melt-blended on an extruder, extruded, and granulated. The resulting granules are dried at 83°C for 12 hours. Finally, standard samples are injected using an injection molding machine, and the samples are placed in the remaining liquid of the antistatic agent.

[0066] The raw materials are melt-blended on a screw extruder, and finally extruded and granulated. The resulting granules are then injected into an injection molding machine. The nozzle temperature of the injection molding machine is controlled at 200℃, the molding cycle is set to 50s, the injection pressure is set to 78MPa, and the screw speed of the extruder is set to 100r / min.

[0067] Finally, antistatic PE plastic product II was obtained.

[0068] The biggest difference between the preparation process of antistatic PE plastic product I and antistatic PE plastic product II is that in the preparation process of antistatic PE plastic product I, the antistatic agent is dissolved in chloroform and an appropriate amount of fixing agent is added to obtain a mixed antistatic agent. In step T3, after the mixed antistatic agent is added to the product, the sample is coated on the surface of the mixed antistatic agent. In contrast, antistatic PE plastic product II adds a single antistatic agent and the sample is coated on the surface of the single antistatic agent.

[0069] The two products were tested according to the requirements of GB / T1410-2006 "Test for Volume Resistivity and Surface Resistivity of Solid Insulating Materials". The surface resistivity test results are shown in the attached figure.

[0070] As shown in the attached figure, antistatic PE plastic product I exhibits stronger antistatic properties than antistatic PE plastic product II. Research has revealed that when antistatic agents are added or coated onto plastic products without a fixing agent, significant amounts of the antistatic agent are lost during drying and storage, resulting in a missing antistatic coating on the surface. However, the addition of a fixing agent stabilizes the antistatic agent's adhesion to the plastic product's interior and surface, preventing large-scale detachment during drying, storage, washing, and other operations. This ultimately improves the plastic product's washability and abrasion resistance, enhancing its antistatic durability and maintaining its volume resistivity. The attached figure illustrates the change in volume resistivity of antistatic PE plastic products I and II over time.

[0071] Example 3: The antistatic PE plastic product includes the following specific raw material components: 120 parts high-density polyethylene, 1 part antioxidant, 30 parts conductive filler, 10 parts antistatic agent, 10 parts coupling agent. The conductive filler substrate is selected as carbon black, the antioxidant is selected as antioxidant 168, the coupling agent is selected as KH-550, and the carbon black in the conductive filler is selected as YM-100B.

[0072] The conductive filler was prepared by passing carbon black through a 400-mesh sieve. Carbon black and an appropriate amount of water were weighed into a beaker, heated and stirred simultaneously at a temperature of 61.5℃. After heating and stirring, the carbon black powder was uniformly suspended on the water surface. An appropriate amount of SnC was weighed... SnCl4·5H2O and SbCl3 were dissolved in another beaker and prepared to a suitable concentration. This solution was then added to the carbon black suspension. HCl was added to adjust the pH to 7.0-7.4, and NaOH solution was added dropwise. Under the controlled pH conditions, the mixture was heated and stirred to allow the added SnCl4·5H2O and SbCl3 to undergo a hydrolysis reaction. Once hydrolysis occurred, the addition of NaOH was stopped. After the hydrolysis reaction was complete, stirring was continued for 20 minutes. The hydrolysis products coated the suspended carbon black particles. The final beaker solution of S3 was filtered, and the filtered product was washed with distilled water. The product was deemed acceptable if no white precipitate was found when tested with AgNO3 solution. The product was then dried at 98℃ and cooled to room temperature. Finally, the desired conductive filler material was obtained by grinding. In S1, the carbon black material had ω(C) ≥ 98.72% and ω(S) ≤ 0.17%.

[0073] The antistatic agent was prepared by adding glycerol and catalyst to a reactor equipped with a gas inlet / outlet device, followed by stirring, vacuuming, and heating. The temperature was raised to 106.4℃ and the vacuum degree was 1.4MPa to completely dissolve the catalyst in the glycerol. The vacuum was then turned off, and glycerol tristearate was added to react. N2 was introduced and the N2 pressure was maintained at 0.17MPa. Heating was continued to raise the temperature to 247.8℃ and reacted for 45 minutes. Heating was then turned off and cooling began. Glycerol tristearate was slowly added, and the cooling rate and the addition rate of glycerol tristearate were controlled. After cooling to 154.9℃, the temperature was maintained for 45 minutes. The reaction was then completed, and the antistatic agent was obtained by cooling.

[0074] Finally, the preparation of antistatic PE plastic products begins. The prepared antistatic agent is dissolved in chloroform, and an appropriate amount of fixing agent is added to obtain a mixed antistatic agent. High-density polyethylene, antioxidant, conductive filler and coupling agent are weighed according to the ratio and mixed with the obtained product. The mixture is melt-blended on an extruder, extruded and granulated, and the obtained granules are dried at 83°C for 12 hours. Finally, standard samples are injected through an injection molding machine, and the samples are placed in the remaining liquid of the mixed antistatic agent.

[0075] PE plastic product samples were immersed in the remaining antistatic agent solution for 2 hours, then removed and ensured that the surface was completely coated. They were then dried in a 48°C oven for 2 hours, and then left at room temperature for 1 hour. The raw materials in T3 were melt-blended on a screw extruder and finally extruded and granulated. The resulting granules were then injected into an injection molding machine. The nozzle temperature of the injection molding machine was controlled at 200°C, the molding cycle was set to 50 seconds, the injection pressure was set to 78 MPa, and the screw speed of the extruder was set to 100 r / min.

[0076] Finally, antistatic PE plastic product III was obtained.

[0077] The biggest difference between the preparation process of antistatic PE plastic product I and antistatic PE plastic product III is that in the preparation process of antistatic PE plastic product I, the flame retardant is mixed with Sb2O3 to obtain a mixed flame retardant, and the product is added in step T3.

[0078] The two products were tested according to the requirements of GB / T1410-2006 "Tests on Volume Resistivity and Surface Resistivity of Solid Insulating Materials". The surface resistivity test results are shown in the attached figure.

[0079] Furthermore, the tensile strength of antistatic PE plastic product I and antistatic PE plastic product III were tested according to GB / T1040.2, and the flame retardant performance was tested according to MT113. The specific test results are shown in the attached figure.

[0080] As shown in the figure above, in summary, the addition of flame retardants weakens the mechanical properties of the resulting antistatic PE plastic products, but can improve their antistatic and flame retardant properties to a certain extent. This is because the introduction of flame retardants causes the gas layer formed during combustion to isolate the plastic products from oxygen, thereby achieving a flame retardant effect. The increased antistatic properties are due to the conductivity of Sb2O3, which increases conductivity while achieving a flame retardant effect, thus preventing the flame retardant from affecting the antistatic properties of the plastic products.

[0081] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus.

[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An antistatic PE plastic product, characterized in that: The invention comprises the following components in parts by weight: 100-150 parts of high-density polyethylene, 1-1.5 parts of antioxidant, 30-50 parts of conductive filler, 10-20 parts of antistatic agent, 5-9 parts of color fixing agent, 1-3 parts of chloroform, 2-3 parts of flame retardant, 10-12 parts of coupling agent and 3-8 parts of Sb2O3, wherein the conductive filler substrate is carbon black.

2. The antistatic PE plastic product according to claim 1, characterized in that: The conductive filler preparation process comprises the following specific steps: S1: Carbon black is screened through 400 mesh, carbon black and appropriate amount of water are weighed into a beaker, and heated while stirring. The heating temperature is controlled at 61.5°C. After stirring and heating, the carbon black powder is evenly suspended on the water surface; S2: Weigh appropriate amounts of SnCl4·5H2O and SbCl3 and dissolve them in another beaker. Prepare to appropriate concentration and then add to the carbon black suspension solution. S3: adding HCl to adjust the pH value to 7.0-7.4, and dripping NaOH solution, under the controlled pH value condition, heating and stirring, so that the added SnCl4·5H2O and SbCl3 undergo hydrolysis reaction, and stopping dripping NaOH after hydrolysis occurs. After the hydrolysis reaction is completed, stirring is continued for 20 minutes, and the hydrolysis product is coated on the suspended carbon black particles; S4: Filter the final beaker solution of S3, wash the filtered product with distilled water, check the AgNO3 solution for white precipitation, dry the water at 98°C, cool at room temperature, and finally grind to obtain the desired conductive filler made of carbon black.

3. The antistatic PE plastic product according to claim 1, characterized in that: The carbon black material of S1 has ω(C)≥98.72% and ω(S)≤0.17%.

4. The antistatic PE plastic product according to claim 1, characterized in that: The preparation of the antistatic agent comprises the following specific steps: Q1: Glycerol and catalyst are added into a reactor with a gas inlet and outlet device, followed by stirring, vacuum and heating. The temperature is raised to 106.4°C and the vacuum degree is 1.4MPa to completely dissolve the catalyst in glycerol. Q2: Turn off the vacuum, add glyceryl tristearate for reaction, introduce N2, maintain the N2 pressure at 0.17 MPa, continue heating to 247.8°C, and react for 45 minutes; Q3: Turn off the heating and start cooling, slowly add glyceryl tristearate, control the cooling speed and the addition speed of glyceryl tristearate, after cooling to 154.9℃, keep warm for 45min, the reaction is completed, and cool to obtain the antistatic agent.

5. The antistatic PE plastic product according to claim 1, characterized in that: The preparation of the Pe plastic product comprises the following specific steps: T1: dissolving the prepared antistatic agent in chloroform, adding an appropriate amount of a color fixing agent to obtain a mixed antistatic agent; T2: Mixing the flame retardant with Sb2O3 to obtain a mixed flame retardant; T3: High-density polyethylene, antioxidant, conductive filler and coupling agent are weighed according to the ratio, mixed with the products obtained from T1 and T2, melt-blended on an extruder, extruded into granules, and the obtained granules are dried at 83°C for 12 hours. Finally, the standard test sample is injected through an injection molding machine, and the test sample is placed in the residual liquid of the mixed antistatic agent.

6. The antistatic PE plastic product according to claim 5, characterized in that: The PE plastic product sample in T3 is immersed in the remaining antistatic agent solution, taken out after 2 hours to ensure that the surface is completely coated, placed in a 48°C oven to dry for 2 hours, and then taken out and kept at room temperature for 1 hour.

7. The antistatic PE plastic product according to claim 6, characterized in that: The raw materials in T3 are melt-blended on a screw extruder and finally extruded into granules. The obtained granules are injection molded in an injection molding machine. The nozzle temperature of the injection molding machine is controlled to 200° C., the molding cycle is set to 50 s, the injection pressure is set to 78 MPa, and the extruder screw speed is set to 100 r / min.

8. The antistatic PE plastic product according to claim 1, characterized in that: The antioxidant is selected as antioxidant 168, the coupling agent is selected as KH-550, and the carbon black in the conductive filler is selected as YM-100B.

9. The antistatic PE plastic product according to claim 1, characterized in that: The flame retardant is selected as (NH4)2HPO4.

Citation Information

Patent Citations

  • Antistatic packaging plastic film

    CN114891291B